Effects of mindset on hormonal responding, neural representations, subjective experience and intake - Franssen, Sieske; Jansen, Anita; van den Hurk, Job; Adam, Tanja; Geyskens, Kelly; Roebroeck, Alard; Roefs, Anne (Physiology & behavior, 2022)
•Study of effect of mindset (loss of control vs. control) on eating variables.•Mindset did not significantly influence brain activity to visual food stimuli.•Ghrelin and GLP-1 levels responded to food intake but not to mindset.•Mindset significantly affected self-reported craving and food intake.•Effect of mindset on physiology, craving, and eating behavior are not in sync. A person can alternate between food-related mindsets, which in turn may depend on one's emotional state or situation. Being in a certain mindset can influence food-related thoughts, but interestingly it might also affect eating-related physiological responses. The current study investigates the influence of an induced ‘loss of control’ mindset as compared to an ‘in control’ mindset on hormonal, neural and behavioural responses to chocolate stimuli. Mindsets were induced by having female chocolate lovers view a short movie during two sessions in a within-subjects design. Neural responses to visual chocolate stimuli were measured using an ultra-high field (7T) scanner. Momentary ghrelin and glucagon-like peptide 1 (GLP-1) levels were determined on five moments and were simultaneously assessed with self-reports on perceptions of chocolate craving, hunger and feelings of control. Furthermore, chocolate intake was measured using a bogus chocolate taste test. It was hypothesized that the loss of control mindset would lead to hormonal, neural and behavioural responses that prepare for ongoing food intake, even after eating, while the control mindset would lead to responses reflecting satiety. Results show that neural activity in the mesocorticolimbic system was stronger for chocolate stimuli than for neutral stimuli and that ghrelin and GLP-1 levels responded to food intake, irrespective of mindset. Self-reported craving and actual chocolate intake were affected by mindset, in that cravings and intake were higher with a loss of control mindset than with a control mindset. Interestingly, these findings suggest that physiology on the one hand (hormonal and neural responses) and behavior and subjective experience (food intake and craving) on the other hand are not in sync, are not equally affected by mindset.